A German version of the Three‐Dimensional Work Fatigue Inventory (3D‐WFI): Factor structure, internal consistency, and correlates. (11th July 2018) - Frone, Michael R.; Reis, Dorota; Ottenstein, Charlotte
Abstract: Work fatigue represents an essential construct for understanding employee health and safety. In this study, we developed and explored the psychometric properties of a German version of the Three‐Dimensional Work Fatigue Inventory and examined a set of hypothesized correlates of work fatigue. Data came from a sample of 439 German workers. Consistent with the original measure, confirmatory factor analyses supported a three‐factor solution (physical, mental, and emotional work fatigue), and estimates of internal consistency reliability exceeded .90 for each dimension of work fatigue. The measure demonstrated a meaningful pattern of associations with predictors (time pressure, job control, psychological detachment, relaxation, and trait negative and positive affect) and an important outcome (work engagement). The German Three‐Dimensional Work Fatigue Inventory will encourage research on an essential construct for employee health and safety using broader populations of workers.